Effects of interventions promoting monitoring of medication use and brief messaging on medication adherence for people with Type 2 diabetes: a systematic review of randomized trials. Issue 5 (17th November 2015) - Farmer, A. J.; McSharry, J.; Rowbotham, S.; McGowan, L.; Ricci‐Cabello, I.; French, D. P.
Abstract: Aims: To assess the impact of interventions promoting the monitoring of medication use and brief messaging to support medication adherence in patients with Type 2 diabetes mellitus, and to investigate the extent of theory use to guide intervention development. Methods: We systematically searched for controlled trials, published from 1990 onwards in Medline, Embase, CINAHL, PsycINFO and the Cochrane library, that evaluated interventions based on monitoring and brief messaging to support medication adherence in patients with Type 2 diabetes, to examine the effectiveness of such interventions. Results: A total of 11 trials, comparing 15 interventions, were identified. Only a small minority presented a low risk of bias. Three interventions were based on delivering brief messages, six were based on monitoring medication adherence, and six used both strategies. Messaging interventions included the use of short message service text messages, web‐based feedback, and messages delivered through monitoring devices. Monitoring interventions included remote self‐reporting of medication and telephone calls with healthcare staff. Improvements in medication adherence were observed in six interventions, although effect sizes were generally moderate. Only two interventions improved both adherence and clinical outcomes. A meta‐analysis of five trials (eight interventions) combining monitoring and messaging strategies showed that the pooled difference in medication adherence between intervention and control was moderate and not statistically significant [standardized mean difference = 0.22 (95% CI −0.05; 0.49)]. Only four trials were based on explicit theoretical frameworks. Conclusions: Although interventions based on messaging and monitoring have the potential to improve medication adherence in patients with Type 2 diabetes, evidence of their efficacy is limited and additional high‐quality, theory‐based research is needed.